If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x-2 = 0
x = 0
x-2 = 0
x-2 = 0
x-2 = 0 // + 2
x = 2
x = 0
x = 0
x in (-oo:0) U (0:2) U (2:+oo)
2/x-2 = (18/(x-2))*(x+4)-4/x+4 // - (18/(x-2))*(x+4)-4/x+4
2/x-((18/(x-2))*(x+4))-(-4/x)-4-2 = 0
2/x-18*(x-2)^-1*(x+4)+4*x^-1-4-2 = 0
(-18*(x+4))/(x-2)+2/x+4/x-4-2 = 0
(-18*x*(x+4))/(x*(x-2))+(2*(x-2))/(x*(x-2))+(4*(x-2))/(x*(x-2))+(-4*x*(x-2))/(x*(x-2))+(-2*x*(x-2))/(x*(x-2)) = 0
2*(x-2)-18*x*(x+4)+4*(x-2)-4*x*(x-2)-2*x*(x-2) = 0
4*x-18*x^2-4*x^2-2*x^2-70*x+8*x+4*x-8-4 = 0
8*x-18*x^2-4*x^2-2*x^2-66*x+4*x-12 = 0
4*x-22*x^2-2*x^2-58*x-12 = 0
-24*x^2-54*x-12 = 0
-24*x^2-54*x-12 = 0
-6*(4*x^2+9*x+2) = 0
4*x^2+9*x+2 = 0
DELTA = 9^2-(2*4*4)
DELTA = 49
DELTA > 0
x = (49^(1/2)-9)/(2*4) or x = (-49^(1/2)-9)/(2*4)
x = -1/4 or x = -2
-6*(x+2)*(x+1/4) = 0
(-6*(x+2)*(x+1/4))/(x*(x-2)) = 0
(-6*(x+2)*(x+1/4))/(x*(x-2)) = 0 // * x*(x-2)
-6*(x+2)*(x+1/4) = 0
( x+1/4 )
x+1/4 = 0 // - 1/4
x = -1/4
( x+2 )
x+2 = 0 // - 2
x = -2
x in { -1/4, -2 }
| 2u-54=-u+21 | | 8a=65-100n | | 400+(15x200)/200 | | (6h-7)/h | | (-7/12)-(-3/8)=0 | | 4x+32=4x+26 | | (17x-9)-8(2x+4)=-5 | | -7/12-(-3/8)=0 | | (10/11)x+(1/3)=(2/5)-(1/11)x+(2/5) | | y=2ZX+2ZY+2XY | | L=0.4L+6 | | -9h=u | | (2/3)x+(1/2)=(3/7)-(1/3)x+(3/7) | | (-2v/9)=-6 | | (-7/2y)=-21 | | [x+3]=7x-4 | | (-5/6v)=20 | | Y=4x-160 | | 5/3x+1/3x=131/3+8/3 | | ln(2x+14)-ln(x+2)=ln(x-5) | | 3(u-5)-9=-6(-2u+2)-u | | 1.89/12 | | 8(v+2)+3v+7=6v+7 | | -2(x-4)-20=-12 | | (5/4)^-3 | | 5-c-2=3+4x+5 | | 6y-3=-6x+3 | | (7/5)^-2 | | 5-x-2=3+4*4x+5 | | -36.812-(-4)+0.007= | | 30=10logx | | 3/8*(-2/-7)*3=0 |